2006
DOI: 10.1103/physrevb.73.155116
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric breakdown and current switching effect in the incommensurate layered compound(LaS)1.196VS2

Abstract: A current switching effect of several orders of magnitude was observed in the incommensurate misfit layered compound ͑LaS͒ 1.196 VS 2 . This effect involves correlated vanadium t 2g states in a hexagonal ͓VS 2 ͔ layer. Application of moderate electric fields ͑ϳ50 V/cm͒ induces a dielectric breakdown and restores a metallic state. The large pretransitional nonlinearities are consistent with a Poole-Frenkel mechanism which highlights the role of Coulomb interactions. This behavior and the strong modulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…[4,5] This could explain the volatile electric-field-induced MIT observed in systems such as Pr 1-x Ca x MnO 3 , [9] La 2-x Sr x NiO 4 , [10] or (LaS) 1.196 VS 2 . [11] Interestingly, (LaS) 1.196 VS 2 and GaTa 4 Se 8 bear some electronic and structural analogies: both compounds contain transition metal clusters and lie in the vicinity of the metal-insulator transition. This urges us to investigate the effects of electric pulses on the electrical transport properties of GaTa 4 Se 8 crystals.…”
mentioning
confidence: 98%
“…[4,5] This could explain the volatile electric-field-induced MIT observed in systems such as Pr 1-x Ca x MnO 3 , [9] La 2-x Sr x NiO 4 , [10] or (LaS) 1.196 VS 2 . [11] Interestingly, (LaS) 1.196 VS 2 and GaTa 4 Se 8 bear some electronic and structural analogies: both compounds contain transition metal clusters and lie in the vicinity of the metal-insulator transition. This urges us to investigate the effects of electric pulses on the electrical transport properties of GaTa 4 Se 8 crystals.…”
mentioning
confidence: 98%
“…We find no appreciable influences of a quasi-periodic potential (8a 2 ≈ 5a 1 = 26.55Å) on electrical conduction and the temperature dependence of the resistivity is quite similar to that of bulk samples. However, preliminary experiments under high-electric-field show the dielectric breakdown and the current switching effect as observed in (LaS) 1.196 VS 2 [22] and one-dimensional Mott insulators Sr 2 CuO 3 and SrCuO 2 [23], which may be related with the destruction of Mott-insulator phases by electric field. They will be discussed in another paper in detail.…”
Section: Electrical and Optical Propertiesmentioning
confidence: 92%
“…This is different from the opening of a gap expected in the weak coupling limit of a CDW. As the compound becomes quite insulating in the process [12], we checked at each temperature that there was no shift due to charging effects [23]. In Fig.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Interestingly, this electronic structure seems to host unconventional behaviors. It has been shown that upon the application of moderate electric fields (≈ 50 V/cm), a current switching leads to a volatile increase of conductivity by 6 orders of magnitude [12]. Such phenomena could be very interesting for applications [13,14].In this paper, we use Angle and Time Resolved Photoelectron Spectroscopy (ARPES and TRPES) to study the interplay of incommensurate distortion, pseudogap and electron-phonon coupling in (LaS) 1.196 VS 2 .…”
mentioning
confidence: 99%